Inelastic stability analysis of uniaxially compressed flat rectangular isotropic CCSS plate - Ibearugbulem, Owus; Eziefula, Uchechi; Onwuka, David Ogbonna (Zielona Góra: Uniwersytet Zielonogórski)
This study investigates the inelastic stability of a thin flat rectangular isotropic plate subjected to uniform uniaxial compressive loads using Taylor-Maclaurin series formulated deflection function. The plate has clamped and simply supported edges in both characteristic directions (CCSS boundary conditions). The governing equation is derived using a deformation plasticity theory and a work principle. Values of the plate buckling coefficient are calculated for aspect ratios from 0.1 to 2.0 at intervals of 0.1.
Keywords: deflection function; plastic buckling; rectangular plate; Taylor`s series; work principle